2021
DOI: 10.2147/ijn.s297933
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Transformation Nanoparticle-Mediated Sonodynamic Therapy: An Effective Modality to Enhance Anti-Tumor Immune Response by Inducing Immunogenic Cell Death in Breast Cancer

Abstract: Purpose Immunologically quiescent of breast cancer cells has been recognized as the key impediment for the breast cancer immunotherapy. In this study, we aimed to investigate the role of nanoparticle-mediated sonodynamic therapy (SDT) in promoting anti-tumor immune of breast cancer cells and its potential immune mechanisms. Materials and Methods The phase-transformation nanoparticles (LIP-PFH nanoparticles) were in-house prepared and its physiochemical characters were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Photothermal therapy and sonodynamic therapy have been demonstrated to boost lymphocyte infiltration and augment the antitumor effects of ICIs (Liang et al., 2019 ; Zhang et al., 2020 ; Si et al., 2021 ) reported that pure oxygen-carrying NPs triggered by US also have the ability to activate antitumor immunity in the body. Combining nanomedicine with immunotherapy is an important method to improve therapeutic effects (Ye et al., 2019 ; Lin et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Photothermal therapy and sonodynamic therapy have been demonstrated to boost lymphocyte infiltration and augment the antitumor effects of ICIs (Liang et al., 2019 ; Zhang et al., 2020 ; Si et al., 2021 ) reported that pure oxygen-carrying NPs triggered by US also have the ability to activate antitumor immunity in the body. Combining nanomedicine with immunotherapy is an important method to improve therapeutic effects (Ye et al., 2019 ; Lin et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…52 Si et al used phase-transformation nanoparticles to demonstrate that nanoparticle-mediated sonodynamic therapy can effectively enhance the antitumor immune response of breast cancer. 53 With the increasing demand for precise and personalized therapeutic treatments, a large number of sonosensitizers with imaging capabilities have been investigated for significantly enhancing treatment efficacy.…”
Section: ■ Advanced Detection Techniquesmentioning
confidence: 99%
“…The results showed that nanoparticle-mediated SDT could promote DC maturation by inducing ICD in breast cancer cells to increase the proportion of cytotoxic T cells. 57 Macrophages have a wide range of biological functions and are essential cells involved in innate immunity and adaptive immunity. 58 Ji et al developed mitochondria-targeted and ultrasound-responsive nanoparticles to co-deliver oxygen (O 2 ) and nitric oxide (NO) to enhance SDT and immune responses.…”
Section: The Mechanism Of Sdtmentioning
confidence: 99%